2006
DOI: 10.1037/0278-6133.25.5.648
|View full text |Cite
|
Sign up to set email alerts
|

Transtheoretical model and condom use in HIV-positive youths.

Abstract: The purpose of the study is to test constructs of the Transtheoretical Model for predicting unprotected intercourse in HIV-positive youths (ages 16-25 years). Questionnaires and interviews about sexual behavior, stage of change, self-efficacy, substance use, emotional distress, and social support were obtained from 60 HIV-positive youths. Path analysis, with standard errors determined by methods appropriate to small samples, suggested that self-efficacy completely mediated the relationship between stage of cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…However, identified correlates of condomless anal and vaginal sex vary across different studies. For instance, several studies with perinatally-infected adolescents reported significant positive associations between substance use and condomless anal and vaginal sex [810], whereas other studies that included both perinatally- and behaviorally-infected youth have not found these same associations [11, 12]. Emotional distress has been positively associated with substance use and subsequent engagement in condomless anal and vaginal sex among YLWH [13, 14] but not consistently [11, 15].…”
Section: Introductionmentioning
confidence: 99%
“…However, identified correlates of condomless anal and vaginal sex vary across different studies. For instance, several studies with perinatally-infected adolescents reported significant positive associations between substance use and condomless anal and vaginal sex [810], whereas other studies that included both perinatally- and behaviorally-infected youth have not found these same associations [11, 12]. Emotional distress has been positively associated with substance use and subsequent engagement in condomless anal and vaginal sex among YLWH [13, 14] but not consistently [11, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, emotional distress has been found to be associated with substance use and subsequent engagement in high-risk sexual behavior in HIV-positive males. 14,15 Exchange sex (i.e., sex in exchange for money, drugs, or other needs) has also been associated with increased risk for acquisition of HIV and sexually transmitted diseases (STDs) among both HIV-positive and HIV negative youth. 16,17 Edwards and colleagues investigated exchange sex and associated characteristics for a representative sample of youth (7 th -12 th grade).…”
Section: Introductionmentioning
confidence: 99%
“…Social support has been found to be positively associated with HIV preventive behaviors including condom use among youth and HIV testing and condom use among women (Gaede et al, 2006; Naar-King et al, 2006; Nyamathi, Stein, & Swanson, 2000; Qiao, Li, & Stanton, 2014). …”
mentioning
confidence: 99%